“More with Less” in Higher Education in Mexico - Rodríguez Gómez , Roberto; Maldonado-Maldonado , Alma (International Higher Education, 2019)
This article analyzes the higher education agenda of the government of Andrés Manuel López Obrador in Mexico as a case of a neopopulist regime. The authors review the trajectory of the agenda, considering campaign promises, the budget projected for higher education during the first year of his presidency, the constitutional educational reform, and the first public policy actions. It reflects on the difficulty to conduct reforms under heavy financial constraints.